The Role of Principals in Academic Supervision to Improve Teacher Performance and Pedagogical Competence: Peran Kepala Sekolah dalam Supervisi Akademik untuk Meningkatkan Kinerja dan Kompetensi Pedagogik Guru - Rahayu, Affandi Rahman Asmoro; Puji Astutik, Anita (Indonesian Journal of Innovation Studies, 2026)
General Background: Quality education depends on effective school leadership and continuous professional support for teachers. Specific Background: At SD Muhammadiyah I Gempol, academic supervision is implemented to address teachers’ performance and pedagogical competence through planned professional guidance. Knowledge Gap: The specific role of principals in organizing, implementing, and following up academic supervision within this school context requires further description. Aims: This study examines the strategic role of the principal in academic supervision to improve teacher performance and pedagogical competence. Results: Descriptive qualitative findings show that planning, classroom observation, constructive feedback, mentoring, training, and follow-up support teacher development. Novelty: The study presents academic supervision as a humanistic, dialogical, collaborative, and continuous professional development process rather than merely administrative control. Implications: Flexible scheduling, open communication, teacher participation, peer support, and continuous professional development are needed to sustain academic supervision. Key Findings Highlights Humanistic feedback encourages teachers to reflect on and improve classroom practices. Seven pedagogical competency areas are strengthened through observation, mentoring, and reflection. Flexible scheduling, teacher readiness, and open communication support continuous supervision. Keywords: Principal Leadership, Academic Supervision, Teacher Performance, Pedagogical Competence, Professional Development